EFIKASI DIRI DAN PROKRASTINASI AKADEMIK MAHASISWA DI STKIP MUHAMMADIYAH SAMPIT - Apuanor Apuanor; Sudarmono Sudarmono; Hosliyah Hosliyah (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
The purpose of this study are: (1) To Know The Effect of Self Efficacy to Achievement Index on Student of The Educational Program Of Economic Studies at STKIP Muhammadiyah Sampit. (2) To Know the Influence of Academic Procrastination on Achievement Index on Student of The Educational Program Of Economic Studies at STKIP Muhammadiyah Sampit. (3) To Know the Influence of Self Efficacy and Academic Procrastination simultaneously on Achievement Index on Student of The Educational Program Of Economic Studies at STKIP Muhammadiyah Sampit.The population in this study are students of The Educational Program Of Economic Studies at STKIP Muhammadiyah Sampit on semester 2, 4, and 6 which amounted to 165 students and taken as a sample of 30% of 51 students with proportionate stratified random sampling technique. The Data analysis technique used is multiple linear regression analysis technique.Based on the results of multiple linear regression analysis are: (1) There is no Effect of Self Efficacy on Achievement Index on Student of The Educational Program Of Economic Studies at STKIP Muhammadiyah Sampit. (2) There is no Influence of Academic Procrastination on Achievement Index on Student of The Educational Program Of Economic Studies at STKIP Muhammadiyah Sampit. (3) No Effect of Self Efficacy and Academic Procrastination collectively to the Achievement Index on the Student of The Educational Program Of Economic Studies at STKIP Muhammadiyah Sampit.